Metacognitive Research in Mathematics Education: a Bibliometric Analysis from 2000 to 2024 - Izzati, Lihar Raudina; Juandi , Dadang (Tematik : Jurnal Konten Pendidikan Matematika, 2025)
Problem-solving ability is one of the four key skills in learning mathematics. One of the factors that influences mathematical solving abilities is metacognitive ability. Metacognitive abilities are a form of advanced thinking skills that include planning, monitoring, and evaluating steps in solving a problem. This study aims to: 1) analyze the annual trend of studies on metacognition in the context of mathematics education research, 2) assess the contribution of the number of publications based on author names, 3) identify the journals that are most active in publishing articles related to metacognitive studies in mathematics education, and 4) analyzing the distribution of the most frequently cited articles in metacognitive studies in mathematics education research. This research is a bibliometric analysis research. There were 115 articles selected into 36 articles from 2000 to 2024. Research articles on metacognitive studies in mathematics education show a steady increase from 2000 to the present, reflecting the growing interest and recognition of the significance of this field. Issues regarding this study after 2022 have been widely raised as research study material so it is still very relevant if there is further research regarding the focus of this study. Writers and journal managers are expected to be able to improve the quality of articles created or managed so that they get lots of citations and have an impact on the focus of metacognitive studies in mathematics education.